Seismic Velocity Structure Along and Across the Ultraslow‐Spreading Southwest Indian Ridge at 64°30′E Showcases Flipping Detachment Faults. Issue 10 (29th September 2021) - Corbalán, A.; Nedimović, M. R.; Louden, K. E.; Cannat, M.; Grevemeyer, I.; Watremez, L.; Leroy, S.
Abstract: We present two ∼150‐km‐long orthogonal 2D P‐wave tomographic velocity models across and along the ridge axis of the ultraslow‐spreading Southwest Indian Ridge at 64°30′E. Here, detachment faults largely accommodate seafloor accretion by mantle exhumation. The velocity models are constructed by inverting first arrival traveltimes recorded by 32 ocean bottom seismometers placed on the two profiles. The velocities increase rapidly with depth, from 3 to 3.5 km/s at the seafloor to 7 km/s at depths ranging from 1.5 to 6 km below the seafloor. The vertical gradient decreases for velocities >7 km/s. We suggest that changes in velocity with depth are related to changes in the degree of serpentinization and interpret the lithosphere to be composed of highly fractured and fully serpentinized peridotites at the top with a gradual downward decrease in serpentinization and pore space to unaltered peridotites. One active and five abandoned detachment faults are identified on the ridge‐perpendicular profile. The active axial detachment fault ( D1 ) shows the sharpest lateral change (horizontal gradient of ∼1 s – 1 ) and highest vertical gradient (∼2 s – 1 ) in the velocities. In the western section of the ridge‐parallel profile, the lithosphere transitions from non‐volcanic to volcanic over a distance of ∼10 km. The depth extent of serpentinization on the ridge‐perpendicular profile ranges from ∼2 to 5 km, with the deepest penetration at the D1 hanging wall. On the ridge‐parallel profile, this depth (∼2.5–4 km) varies less as the profile crosses the D1 hanging wall at ∼5–9 km south of the ridge axis. Plain Language Summary: We investigate the Southwest Indian Ridge lithosphere at 64°30′E, where the Somalian and Antarctic plates move slowly away from each other at less than 14 mm/year. This is one of a limited number of places on Earth where mantle is currently being exhumed to the seafloor. We use seismic sensors, placed across and along the ridge axis, to analyze how seismic waves travel from the energy sources, through the lithosphere, to these sensors. Our results, in the form of two‐dimensional velocity models, show that the rock velocities increase rapidly with depth. Lateral and vertical velocity changes delimit a system of detachment faults on the ridge‐perpendicular profile, responsible for bringing mantle‐derived rocks, peridotites, up to the seafloor. Based on the modeled velocities and velocity changes, and previous extensive seafloor sampling, we suggest that ∼75% of the lithosphere in the study area is composed of highly fractured and fully hydrothermally altered peridotites at the top with a gradual downward decrease in alteration and pore space to unaltered peridotites at depth. We also locate the transition to lithosphere with a magmatic component in the western section of the ridge‐parallel profile. Key Points: First detailed 2D regional P‐wave velocity models across and along an ultraslow‐spreading Southwest Indian Ridge amagmatic segment A system of flipping detachments is imaged in the subsurface for the first time constrained by the velocity structure Lithosphere gradually transitions from highly fractured and fully serpentinized peridotites at the top to unaltered peridotites at depth